Energy constraint and compensation: Insights from endurance athletes - Dolan, E.; Koehler, K.; Areta, J.; Longman, D. P.; Pontzer, H. (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology, 2023)
The Constrained Model of Total Energy Expenditure predicts that increased physical activity may not influence total energy expenditure, but instead, induces compensatory energetic savings in other processes. Much remains unknown, however, about concepts of energy expenditure, constraint and compensation in different populations, and it is unclear whether this model applies to endurance athletes, who expend very large amounts of energy during training and competition. Furthermore, it is well-established that some endurance athletes consciously or unconsciously fail to meet their energy requirements via adequate food intake, thus exacerbating the extent of energetic stress that they experience. Within this review we A) Describe unique characteristics of endurance athletes that render them a useful model to investigate energy constraints and compensations, B) Consider the factors that may combine to constrain activity and total energy expenditure, and C) Describe compensations that occur when activity energy expenditure is high and unmet by adequate energy intake. Our main conclusions are as follows: A) Higher activity levels, as observed in endurance athletes, may indeed increase total energy expenditure, albeit to a lesser degree than may be predicted by an additive model, given that some compensation is likely to occur; B) That while a range of factors may combine to constrain sustained high activity levels, the ability to ingest, digest, absorb and deliver sufficient calories from food to the working muscle is likely the primary determinant in most situations and C) That energetic compensation that occurs in the face of high activity expenditure may be primarily driven by low energy availability i.e., the amount of energy available for all biological processes after the demands of exercise have been met, and not by activity expenditure per se.